Between Serbia, America and Britain: a Sociolinguistic View of the Writings of Mabel St. Clair Stobart and Jelena Lozanić (Knjiženstvo, journal for studies in literature, gender and culture, 2024)
This paper deals with the construction of a complex sociolinguistic narrative network of meaning that includes intricate interaction of societies and individuals, local and global, based on narratives written by two female authors about personal experiences from the First World War: Mission for Serbia: Letters from America and Canada 1915-1920 (1970) by Jelena Lozanić Frothingham and The Flaming Sword in Serbia and Elsewhere (1916) by Mabel St. Clair Stobart. The authors presented their own experience of the war and the complexity of a woman’s identity, while they were relocated to a different environment – Jelena Lozanić from Serbia to the United States of America and Canada, and Mabel Stobart from England to Serbia. Through the sociolinguistic narrative network of these works, we discover new positions of power that women won by actively participating in the First World War, regardless of geographical distance, the diversity of their positions, roles, and environments. The messages of humanism and pacifism are addressed to the readers of both works, while concrete examples show how much an individual can achieve for the community through active social engagement. Reading these works and searching for the texts related to them, we ourselves become part of the same sociolinguistic narrative network (Filipović, 2018a: 219) as interpreters of social relations shown from the particular positions of the authors.
Keywords: World War I; women; sociolinguistic narrative network